A PROPOSAL OF CRITERIA TO EVALUATE AND RE-DESIGN SUSTAINABLE PRODUCTS - Flores Calderón, Alejandro (My University, 2011)
Sustainable Products, Design For sustainability, Sustainability criteria
Keywords: Sustainable Products, Design For sustainability, Sustainability criteria